2011
DOI: 10.1007/s10103-011-1038-3
|View full text |Cite
|
Sign up to set email alerts
|

Neodymium:YAG laser treatment of lower leg telangiectasia: a new minimally invasive approach

Abstract: The aim of this study was to validate the safety and effectiveness of a new therapeutic procedure for the treatment of lower leg telangiectasia without clinical vein insufficiency. A group of 20 healthy women aged between 24 and 47 years (mean±sem 37.05 ± 1.47) with lower leg telangiectasia without clinical vein insufficiency, previously investigated by echo colour Doppler sonography, were recruited and were treated with neodymium:YAG laser (mean±sem 2.5 ± 0.11 sessions). Good or excellent results were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Rogachefsky et al reported the effectiveness of 1064‐nm Nd:YAG in telangiectasia and small reticular veins on 21 lower extremity sites . Iannitti et al reported good or excellent results in 16 patients in their study of 20 healthy women …”
Section: Discussionmentioning
confidence: 90%
“…Rogachefsky et al reported the effectiveness of 1064‐nm Nd:YAG in telangiectasia and small reticular veins on 21 lower extremity sites . Iannitti et al reported good or excellent results in 16 patients in their study of 20 healthy women …”
Section: Discussionmentioning
confidence: 90%